New record of the endemic jewel beetle Pygicera scripta krahmeri (Coleoptera, Buprestidae, Nacionini) from a coastal forest of Hualpén, Biobío Region, Chile - Barahona-Segovia, Rodrigo M.; Pañinao-Monsálvez, Laura (Zootaxa, 2020)
Pygicera Kerremans, 1903 is an endemic genus of jewel beetle of Chile distributed in the central Chile hotspot, which is distributed from the Atacama Desert in the north to the Valdivian Forest in the south (Myers et al., 2000). Currently, Pygicera is composed of one species and two subspecies: Pygicera scripta scripta Laporte & Gory, 1837 and the Valdivian rainforest subspecies Pygicera scripta krahmeri Moore 1981 (Figs 2–6). The first subspecies is distributed from Limarí in the Coquimbo Region to Curicó in the Maule Region, both in the coast as well as Andean foothills. This is considered the common subspecies (Moore, 1981; Moore & Vidal, 2015). The southern subspecies is distributed from Victoria in the Araucanía Region to La Unión in Los Ríos Region (Moore, 1981; Moore & Vidal, 2015) and is the rarest and less abundant subspecies. The larvae of both subspecies have been recorded in the “maitén” (Maytenus boaria) Molina, from which they have been reared (Moore, 1981, 1987; Moore & Vidal, 2015).